Time and cost performance analysis: earned value management method on HPK Project Using Mobox - Vegit Risana Hughes; Susetyo, Budi (Teknisia, 2024)
Conventional construction methods have proven inadequate for meeting the accelerated development needs of IKN, highlighting the necessity for innovative approaches to expedite construction. Additionally, challenges related to material supply further exacerbate the situation. The Mobox method emerges as a promising alternative, offering potential to streamline project completion. This study compares time performance between conventional concrete methods, which typically require 7 months, and the Mobox method, which achieves the same in 4 months. The aim is to evaluate whether time and cost performance align with the project owner's expectations, using the Earned Value Management (EVM) method for a 4-storey building project utilizing Mobox modular construction. At week 16, the project’s time performance met expectations, as evidenced by a Schedule Variance (SV) of zero and a Schedule Performance Index (SPI) of 1. Cost performance also exceeded expectations, with a positive Cost Variance (CV) of Rp 11,784,790,045.29 and a Cost Performance Index (CPI) of 1.023, indicating cost efficiency. The Mobox method, coupled with the EVM approach, proves to be an effective and efficient alternative for construction projects, demonstrating the capability to complete projects on time and within budget while maintaining quality.